2003
DOI: 10.1242/jcs.00237
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sp1 phosphorylation as a mechanism of hepatocyte growth factor (HGF/SF)-induced vascular endothelial growth factor (VEGF/VPF) transcription

Abstract: Hepatocyte growth factor (HGF/SF)-induced expression of vascular endothelial growth factor (VEGF/VPF) has been implicated in paracrine amplification of angiogenesis, contributing to angiogenic responses during inflammation, wound healing, collateral formation and tumor growth. We have shown previously that HGF/SF-mediated VEGF/VPF expression by keratinocytes is primarily dependent on transcriptional activation, and we mapped the HGF/SF-responsive element to a GC-rich region between bp -88 and -65. Sp1-like fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 56 publications
5
62
0
Order By: Relevance
“…Experiments of Sp1 immunoprecipitation performed to evaluate the presence of serine-and threonine-phosphorylated proteins revealed increased intracellular amounts of serine-phosphorylated Sp1 in response to Bcl-2 overexpression. In agreement with other reports, demonstrating that Sp1 phosphorylation of serine residues correlates with enhanced transcription of "Sp1 site-dependent" genes (31,34), we hypothesized that Bcl-2 is involved in the increase of Sp1 transcriptional activity through serine phosphorylation of the transcription factor. MTR, a pharmacological inhibitor of Sp1, prevented the induction of Sp1 DNA binding activity and uPAR expression by Bcl-2, thus confirming the role of Sp1 in Bcl-2-induced uPAR expression.…”
Section: Bcl-2 In Upar Expression and Sp1 Transcriptional Activitysupporting
confidence: 91%
See 2 more Smart Citations
“…Experiments of Sp1 immunoprecipitation performed to evaluate the presence of serine-and threonine-phosphorylated proteins revealed increased intracellular amounts of serine-phosphorylated Sp1 in response to Bcl-2 overexpression. In agreement with other reports, demonstrating that Sp1 phosphorylation of serine residues correlates with enhanced transcription of "Sp1 site-dependent" genes (31,34), we hypothesized that Bcl-2 is involved in the increase of Sp1 transcriptional activity through serine phosphorylation of the transcription factor. MTR, a pharmacological inhibitor of Sp1, prevented the induction of Sp1 DNA binding activity and uPAR expression by Bcl-2, thus confirming the role of Sp1 in Bcl-2-induced uPAR expression.…”
Section: Bcl-2 In Upar Expression and Sp1 Transcriptional Activitysupporting
confidence: 91%
“…Increased Sp1 phosphorylation and activity has also been proposed to result from oxidative stress-, tumor necrosis factorand hepatocyte growth factor-induced VEGF transcription (34,35,59). Thus, it is likely that this transcription factor also plays a role in Bcl-2-induced VEGF expression that we previously demonstrated (15,16).…”
Section: Bcl-2 In Upar Expression and Sp1 Transcriptional Activitymentioning
confidence: 53%
See 1 more Smart Citation
“…46 IL-6 is known to signal primarily via the STAT and MAPK pathways. 35 In contrast to HGF-induced VEGF transcription, where Sp1 phosphorylation is dependent on PI3-K and MEK1/2 signalling, 47 pretreatment of NIH3T3 cells with either PD98059 or LY294002 led only to a 30% reduction of IL-6-triggered VEGF transcription (data not shown), suggesting that the MAPK and PI3-K/Akt signaling pathways are only partially involved. However, transfection of NIH3T3 cells and U87MG cells with dominant-negative STAT3 reduced IL-6-mediated VEGF expression to control levels, attesting that STAT3 is absolutely required for IL-6-regulated VEGF expression.…”
Section: Discussionmentioning
confidence: 96%
“…Because threonine 453 phosphorylation of Sp1 was shown to increase its DNA binding and/or transcriptional activities toward target genes including VEGF (37-39), increased threonine phosphorylation of Sp1 by CD81 signaling is likely a mechanism of CD81-induced MT1-MMP transcription in melanoma cells. Meanwhile, the ERK, Akt, and JNK pathways are implicated in increasing Sp1 phosphorylation in various cell systems (38,40). Interestingly, Carloni et al (41) found that CD81 increases synthesis of phosphoinositides by activating the associated PI4K, leading to phosphoinositide-facilitated membrane translocation of Shc in hepatic tumor cells.…”
Section: Discussionmentioning
confidence: 99%